Analisis Kebijakan Kepala Sekolah pada Pelaksanaan Kurikulum Merdeka di MTs Aisyiyah Binjai - M. Ilyasa Ramadhan (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to analyze the policies implemented by the Principal at Madrasah Tsanawiyah (MTs) Aisyiyah Binjai regarding the independent curriculum. The Merdeka Curriculum is an innovation that demands a change in paradigm in the implementation of education in Indonesia. The research method used is a qualitative approach with a case study type. Data collected through interviews and observations. The results of this research found that the principal's policies included: implementing the P5P2RA project, the principal providing independent curriculum planning training to educators through IKM training/workshops, the principal making a peer tutoring policy and the principal also holding educational unit reflections periodically. This research is expected to provide in-depth insight into the policies implemented by the principal of MTs Aisyiyah Binjai. It is hoped that this research can become a reference for schools, teachers and policy makers in increasing the effectiveness of implementing the Independent Curriculum.